Design and Implementation Of Software Simulation Aircrsft Flight Controls and Monitoring - RAKESH VYAS, RAHUL MISHRA, UDAY KIRAN ANVEKAR and AMIT PRASAD (2009)
INNTERNAL Guide : Kesavan M V EXTERNAL Guide: Patel M S USN No : 1MJ06CS078, 1MJ06CS075, 1MJ06CS107 and 1MJ03CS003 Carried out at : Intaglio Systems Pvt Ltd Bangalore- Acc No : PR1719 Project Report CD No : RC93
Keywords: Computer Science